One‐pot Facile Synthesis of Multifunctional Conjugated Microporous Polymers via Suzuki‐Miyaura Coupling Reaction. Issue 4 (27th January 2020) - Teng, Dao‐Guang; Wei, Xian‐Yong; Li, Jia‐Hao; Gao, Hua‐Shuai; Zhang, Min; Zong, Zhi‐Min
Abstract: A wide set of conjugated microporous polymers (CMPs) are synthesized via a facile Pd‐catalyzed Suzuki‐Miyaura coupling reaction between organo‐boron reagents and organic halides in the presence of K2 CO3 . According to multiple characterizations, the resulting polymers are thermally stable and fluorescent with large specific surface areas (SSAs) and narrow pore distributions. Especially, polymer synthetized by using 1, 3, 6, 8‐tetrabromopyrene (TBP) and 1, 4‐phenylenediboronic acid (PDBA) exhibits the largest apparent SSA up to 1071 m 2 g −1, H2 uptake capacity of 152.77 cm 3 g −1 (77 K, 1 bar) and CO2 uptake capacity of 58.97 cm 3 g −1 (273 K, 1 bar). Furthermore, parallel experiments prove TBP and PDBA are the best building blocks for these series polymers synthesis. Moreover, CMPs feature large SSAs, outstanding thermal and fluorescent performances, and facile preparation, making themselves promising candidates for the future industrial applications. Abstract : Conjugated microporous polymer synthetized using 1, 3, 6, 8‐tetrabromopyrene and 1, 4‐phenylenediboronic acid exhibits the largest SSA up to 1071 m 2 g −1, H2 uptake capacity of 152.77 cm 3 g −1 (77 K, 1 bar) and CO2 uptake capacity of 58.97 cm 3 g −1 (273 K, 1 bar). Moreover, the facile preparation strategy, outstanding thermal and fluorescent performances and high SSAs make CMPs promising candidates for the future industrial applications.